Magnetic damping constant in Co-based full heusler alloy epitaxial films. (29th April 2015) - Oogane, M; Kubota, T; Naganuma, H; Ando, Y
Abstract Co-based full-Heusler alloys, such as Co2MnSi and Co2MnGe, are expected to be used as half-metallic ferromagnetic material, which has complete spin polarization. They are the most promising materials for realizing half-metallicity at room temperature due to their high Curie temperature. The optimization of the magnetic damping constant of ferromagnetic materials is extremely important for achieving high-speed magnetization switching and reducing critical current density for spin torque transfer switching. We have systematically investigated the magnetic damping constant in Co-based full Heusler alloy epitaxial films. We found that the Gilbert damping constant seems to be roughly proportional to the total density of states at the Fermi level (EF) by first principle calculation. A very small magnetic damping constant of 0.003 in the Co2Fe0.4Mn0.6Si epitaxial film was demonstrated. The small magnetic damping constant in Co2FexMn1−xSi films with x < 0.6 can be attributed to the half-metallicity of Heusler alloys. Co-based full Heusler alloys with both half-metallicity and small magnetic damping will be very useful for future applications based on spintronic devices.